The Internet of Things for Water Quality Control Systems on Freshwater Fish Lake Tondano Farming - Tentero, Jenifer Yunisha; Djamen, Arje Cerullo; Batmetan, Johan Reimon (International Journal of Information Technology and Education, 2024)
Freshwater fish farming is an important segment in the fisheries industry that requires extraordinary consideration of water quality to ensure optimal fish welfare and growth. This research creates an Online of Things (IoT)-based water quality control framework to monitor and control basic parameters in freshwater fish farming lakes, such as temperature, pH, turbidity, and water particle levels. The framework consists of sensors associated with the ESP32 microcontroller, which can collect data in real-time. The information is then sent to the IoT stage using a Wi-Fi network, enabling checks that cannot be accessed via the web or portable applications. In addition, the system is equipped with mechanization instruments to direct water conditions, such as moving the aerator or radiator automatically based on known parameters. The tests showed that this skeleton can accurately filter water quality and provide a quick reaction to changes in natural conditions. The use of this framework is expected to increase effectiveness and efficiency in the development of freshwater fish, as well as reduce the possibility of fish passing by due to poor water quality, Therefore, this IoT-based water quality control framework is an imaginative solution that can support the sustainability and increase of production in the development of freshwater fish.